Ecorregiones dulceacuícolas de Colombia: una propuesta para la planificación territorial de la región trasandina y parte de las cuencas del Orinoco y Amazonas (2016)
Colombia is a geographically diverse country mainly due to the Andean terrain, which creates a river system that combines different orders of drainages, physiography and water types, located in four areas: Caribbean, Pacific, Orinoco and Amazon. Hydrographic areas or basins are classified based on the watershed and have been treated regionally only in terms of political division to manage watersheds sections. A regional classification of freshwater ecosystems that combines both geographical and biological criteria, does not exist for Colombia, so the territorial planning and decision-makers do not consider aquatic ecosystems as a unit in their management guidelines. Therefore, the objective of this research was to propose continental hydro-biological units based on hydro-geographic and biological criteria, regrouping official hydrographic areas according to their fish species composition and the interpretation of their drainage network and geomorphological characteristics. There are 28 ecoregions proposed: six for the Caribbean region, eight for the Andean, five for the Pacific and nine for cis-Andean (five for Orinoco and four for Amazonas). These ecoregions can be used as a tool of territorial planning.